Flow bouncing and electron injection observed by Cluster. Issue 5 (20th May 2013) - Nakamura, R.; Baumjohann, W.; Panov, E.; Volwerk, M.; Birn, J.; Artemyev, A.; Petrukovich, A. A.; Amm, O.; Juusola, L.; Kubyshkina, M. V.; Apatenkov, S.; Kronberg, E. A.; et al.
Abstract : [1] Characteristics of particles and fields in the flow‐bouncing region are studied based on multipoint observations from Cluster located at 13–15 RE downtail during a substorm event around 12:50 UT on 7 September 2007. The Cluster spacecraft were separated by a distance of up to 10, 000 km and allowed to determine the mesoscale evolution of the current sheet as well as the development of the dipolarization front. We show that the flow bouncing took place associated with a tailward‐directedj ×B force in a disturbed current sheet in addition to an enhanced tailward pressure gradient force. Multiple Earthward propagating dipolarization fronts accompanied by enhanced flux of energetic electrons were observed before the flow bouncing. The sequence of events started with a localized dipolarization front and ended with a large scale (>10 RE ) dipolarization front accompanied by a major increase in energetic electrons at all spacecraft and immediately followed by flow bouncing. Multiple dipolarization fronts result in the formation of compressed magnetic field with a plasma bulge bounded by thin ion‐scale current layers, a favorable condition for flow bouncing. These observations suggest that to understand the flow bouncing and related acceleration of plasma in the near‐Earth tail, both the large‐scale MHD properties and the transient and small‐scale effect of the plasma interaction with the Earth‐dipole field need to be taken into account. Key Points: Dusk‐to‐dawn current identified during the flow bouncing Plasma bulge region with a few ion scale boundaries in flow braking region Electron injection related to dipolarization front and flow braking